Beans and rice in Brazilian lexicon and culture - Tscherkas, Márcia (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Food is, above all, culture. If we consider language as a vehicle, a product, and a producer of culture (Galisson, 1991), it is essential to combine language and culture in foreign language teaching. Thus, we decided to carry out work on the text genre: chronicle, to analyze the occurrence of lexis that is culturally marked by the main dish of Brazilian cuisine: feijão com arroz (beans and rice). In addition to gastronomy, we can find other uses of feijão com arroz, such as the sense of being complete, the same, trite, and trivial, and also identify if there is a difference in word order: beans and rice vs. rice and beans in Brazilian sense of humor in four Brazilian chronicles. Considering the context, this material could be relevant for the study of the teaching and learning of Brazilian as a foreign language